Developing an Integrated Capital Assistance and Community Training System Using Agile Scrum - Zuhdi, Ahmad Muzaki; Lutfina, Erba; Saraswati, Galuh Wilujeng (Politeknik Ganesha Medan, 2026)
Local governments increasingly require Cross-Agency Integration platforms to deliver transparent, auditable public services, yet capital assistance and community training programs are often managed through fragmented applications and manual workflows, leading to duplicated data, slow verification, and limited status traceability. This study develops an integrated capital assistance and community training system for local government using Agile Scrum, and evaluates its functional acceptance, usability, and security readiness to support Public Service Digitalization. Requirements were elicited through observation and interviews across three service-managing municipal agencies, while system governance and evaluation also involved the Communication and Informatics Office. The system was implemented as a web application with iterative sprints and backlog prioritization. Evaluation employed a User Acceptance Test (Likert 1–5, 10 items), System Usability Scale, and penetration testing using OWASP ZAP focusing on session management and HTTP security headers. Fifteen agency users participated in the evaluation. The system achieved 93% functional acceptance and a System Usability Scale score of 82.3, indicating excellent perceived usability. Security scanning found no high-risk issues, while medium- and low-risk findings were dominated by missing headers (Content Security Policy and X-Frame-Options) and incomplete cookie flags, which can be mitigated through standard hardening. The proposed platform improves cross-agency coordination and citizen-facing transparency while meeting usability expectations. Agile Scrum enabled rapid alignment with stakeholders and incremental quality improvements. Future work includes analytics, financial-system integration, and continuous security monitoring.